2012
DOI: 10.1086/667229
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of a Neotropical Clade in the Gesneriaceae: More Tales of Convergent Evolution

Abstract: The Gesneriaceae is a family known for convergent evolution of complex floral forms. As a result, defining genera and resolving evolutionary relationships among such genera using morphological data alone has been challenging and often does not accurately reflect monophyletic lineages. The tribe Episcieae is the most diverse within Neotropical Gesneriaceae in terms of its number of species and morphological diversity. As a result, defining genera using floral characters has been historically troublesome. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 63 publications
(114 reference statements)
6
41
1
6
Order By: Relevance
“…When compared to Gesneriaceae species occurring in the Amazon and Guyana shield, these specimens from Serra do Aracá share some similarities in habit and flower morphology with the genus Lesia J.L.Clark & J.F.Sm., which has been recently segregated from Nematanthus, based on phylogenetic evidence (Smith and Clark 2013). As currently defined Lesia comprises a single species, Lesia savannarum that occurs in rain forests at low and medium elevation along a periAmazonian arc from the Andes foothills in eastern Peru to Colombia, northern Brazil (Amazonas and Roraima) and the Guyana Shield (Skog and Feuillet 2008;Smith and Clark 2013 (Clark et al 2006(Clark et al , 2012Chautems and Perret 2013). A better resolution of the relationships among these morphologically distinct taxa is, however, needed to further explore how flower and biogeographic distribution have evolved in this clade.…”
Section: Introductionmentioning
confidence: 99%
“…When compared to Gesneriaceae species occurring in the Amazon and Guyana shield, these specimens from Serra do Aracá share some similarities in habit and flower morphology with the genus Lesia J.L.Clark & J.F.Sm., which has been recently segregated from Nematanthus, based on phylogenetic evidence (Smith and Clark 2013). As currently defined Lesia comprises a single species, Lesia savannarum that occurs in rain forests at low and medium elevation along a periAmazonian arc from the Andes foothills in eastern Peru to Colombia, northern Brazil (Amazonas and Roraima) and the Guyana Shield (Skog and Feuillet 2008;Smith and Clark 2013 (Clark et al 2006(Clark et al , 2012Chautems and Perret 2013). A better resolution of the relationships among these morphologically distinct taxa is, however, needed to further explore how flower and biogeographic distribution have evolved in this clade.…”
Section: Introductionmentioning
confidence: 99%
“…Based on molecular phylogenetic studies, Clark et al (2006Clark et al ( , 2012 and Perret et al (2013) reported the close relationship of Nematanthus australis Chautems and N. wettsteinii to the genus Codonanthe, with both species nesting within Codonanthe. Through pollen grains observations of N. wettsteinii, it was found that the pollen morphology supported such a placement.…”
Section: Discussionmentioning
confidence: 99%
“…and Nematanthus Schrader] and by the presence of sepals connate at the base and an urceolate cup or funnel-shaped calyx (Wiehler, 1983;Clark et al, 2006). Molecular data shows that the tribe represents a monophyletic clade with a heterogeneous morphology within the Gesneriaceae (Smith & Carroll, 1997;Smith, 2000aSmith, , 2000bZimmer et al, 2002;Clark et al, 2006Clark et al, , 2012.…”
mentioning
confidence: 99%
“…Display capsules and their contrasting color effects are assumed to attract seed dispersing animals in Drymonia and related genera (Wiehler 1983, Weber 2004, 2012. For the fleshy and irregularly dehiscent capsules of Solenophora calycosa Donnell Smith (1898: 152), Weber & Weissenhofer (2007) suggested that the contrast provided by the fruit wall (orange) and the placentae plus seeds (deep red) is attractive to birds and/or small mammals.…”
Section: Putative Function Of Fruit Rupturementioning
confidence: 99%